Building a Suitability Scoring System for the Redevelopment of an Existing Park into an Inclusive Park for Disabled: Case Studies from Pathum Thani, Thailand - Selanon, Pattamon; Puggioni, Federico; Dejnirattisai, Supanut; Sapsangthong, Akarawit; Rutchamart, Autchariya (Thammasat Review, 2022)
The northern fringes of the Bangkok urban area show common traits in terms of urban physical layout, social composition, urban development processes. Specifically, these territories have in common their progressive loss of agricultural activities, the urbanisation, the presence of industries and educational institutions, the daily commuting towards Bangkok’s core, the car dependency (Likitsawat and Sahavacharin, 2022); all these factors influence the quality of life of these rapidly growing territories, and consequently, their inclusivity. This article investigates in detail the need of inclusive accessible green spaces in one of these peripheral areas, Thaklong – Klongluang-Rangsit in the Pathum Thani Province. Here, the actual dotation of public parks is reduced and concentrated in six locations not connected among themselves. The need of a change of paradigm in the concept of “inclusive parks” affects not only the urban policies, but diverse aspects of the landscape discipline: the integration with the surroundings, the accessibility, the perception and the interpretation of the ideas of disability and self-use – especially the disabled, the detail design of the spaces. The main objective of this research is the analysis of the six parks in Thaklong–Klongluang-Rangsit with the Suitability Scoring System (SSS), an index developed in this article and valid for other comparable urban contexts, which includes a diagrammatic visualisation of the results. The analysis, based on physical and urban considerations, will provide a score, rating of the likeability for a specific park to be developed and improved in terms of inclusivity and accessibility for the disability carriers. The discussions will provide points useful to analyse and develop other parks in similar peri-urban areas in Bangkok and similar contexts.